To remove the parentheses, you just distribute.
So, it will become 3ax + 3b^2 - 3c +2. I don't think there is any like term in this expression.
Answer:
107%
Step-by-step explanation:
because if we look at the x-axis, Discount (%)
and look at 35 which is between 30 and 40
and start going up we get near 100
so
107%
or?
we use the two points and with that we find the slope first
![\frac{y2-y1}{x2-x1}](https://tex.z-dn.net/?f=%5Cfrac%7By2-y1%7D%7Bx2-x1%7D)
plug in (20,62) and (10,32)
equals
![\frac{-30}{-10}](https://tex.z-dn.net/?f=%5Cfrac%7B-30%7D%7B-10%7D)
simplify to 3
then we use
y - y1 = m (x - x1)
y - 62 = 3 (x - 20)
y - 62 = 3x - 60
add 60 from both sides
y - 2 = 3x
add 2 to both sides
y=3x+2
then plug in 35
y= 3(35) + 2
which is
107
Answer:
The solved given fractional expression is ![\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B3%7D)
Therefore the given fractional expression becomes
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
Step-by-step explanation:
Given fractional expression is ![\frac{6}{2}+\frac{8}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D)
To solve the given fractional expression as below :
![\frac{6}{2}+\frac{8}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D)
( here taking the term 3 as LCM )
( by adding the sums here )
![=\frac{17}{3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B17%7D%7B3%7D)
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
Therefore the solved given fractional expression is ![\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B3%7D)
Therefore the given fractional expression becomes
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
The solved given fractional expression is ![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
Answer:
Let
Total number of people (T)=1600
those satisfied with the car (t) =720
The percentage of the satisfied people(S)= number of satisfied people divided by the total number of people who took part in the survey, multiplied by 100
=> S=(T/t)*100
S=(720/1600)*100
S=45%
Step-by-step explanation: